Economic dynamics : an introduction - Baumol, William J. (New York: Macmillan, 1959)
This book is largely based on a series of lectures the author gave at the London School of Economics in the two academic years 1947 - 1949. The edition covers: The Magnificent Dynamics; Statics Involving Time; Process Analysis; Single Equation Models; Simultaneous Equation Models.
Includes bibliography.
rpm 03/10/2017
Loans
Keywords: Economics; Statics and dynamics (Social sciences)